Failure mechanism of sandwich beams subjected to three-point bending. (1st December 2015) - Banghai, Jiang; Zhibin, Li; Fangyun, Lu
Abstract: An analytical solution for the failure modes of foam-core sandwich beams subjected to three-point bending is presented in this study and a failure model is established to predict the failure modes and estimate the initial failure loads for each failure mode, i.e. face yield, core shear and indentation. Quasi-static three-point bending experiments have been carried out to verify the predictions of the theoretical analysis. Analytical predictions of the failure mode and the ultimate load compare well with the experimental results and better accuracy than the previous model is achieved.